Missing link between tissue specific expressing pattern of ERβ and the clinical manifestations in LGBLEL - Zhang, Xujuan; Zhao, Pengxiang; Ma, Mingshen; Wu, Hao; Liu, Rui; Liu, Ziyi; Cai, Zisong; Liu, Mengyu; Xie, Fei; Ma, Xuemei (Frontiers in Medicine, 2023)
Purpose Lacrimal gland benign lymphoepithelial lesion (LGBLEL) is an IgG4-related disease of unknown etiology with a risk for malignant transformation. Estrogen is considered to be related to LGBLEL onset. Methods Seventy-eight LGBLEL and 13 control clinical samples were collected and studied to determine the relationship between estrogen and its receptors and LGBLEL development. Results The serological analysis revealed no significant differences in the levels of three estrogens be-tween the LGBLEL and control groups. However, immunohistochemical analyses indicated that the expression levels of ERβ and its downstream receptor RERG were relatively lower in LGBLEL samples than in control samples, with higher expression in the lacrimal gland and lower expression in the lymphocyte infiltration region. However, low expression of ERα was detected. The transcriptome sequence analysis revealed upregulated genes associated with LGBLEL enriched in lymphocyte proliferation and activation function; downregulated genes were enriched in epithelial and vascular proliferation functions. The key genes and gene networks were further analyzed. Interactions between B cells and epithelial cells were analyzed due to the identified involvement of leukocyte subsets and epithelial cells. B cell proliferation was found to potentially contribute to lacrimal gland apoptosis. Conclusion Therefore, the tissue-heterogeneous expression pattern of ERβ is potentially related to the clinical manifestations and progression of LGBLEL, although further investigations are required to confirm this finding.